Associations of Renalase With Blood Pressure and Hypertension in Chinese Adults - Wang, Yang; Chen, Chen; Hu, Gui-Lin; Chu, Chao; Zhang, Xiao-Yu; Du, Ming-Fei; Zou, Ting; Zhou, Qing; Liao, Yue-Yuan; Ma, Qiong; Wang, Ke-Ke; Sun, Yue; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Renalase, a novel secretory flavoprotein with amine oxidase activity, is secreted into the blood by the kidneys and is hypothesized to participate in blood pressure (BP) regulation. We investigated the associations of renalase with BP and the risk of hypertension by examining renalase single nucleopeptide polyporphims (SNPs), serum renalase levels and renal expression of renalase in humans. Methods: ① Subjects (n = 514) from the original Baoji Salt-Sensitive Study cohort were genotyped to investigate the association of renalase SNPs with longitudinal BP changes and the risk of hypertension during 14 years of follow-up. ② 2392 participants from the Hanzhong Adolescent Hypertension Study cohort were used to examine the association of serum renalase levels with hypertension. ③ Renalase expression in renal biopsy specimens from 193 patients were measured by immunohistochemistry. Renalase expression was compared in hypertensive vs. normotensive patients. Results: ① SNP rs7922058 was associated with 14-year change in systolic BP, and rs10887800, rs796945, rs1935582, rs2296545 and rs2576178 were significantly associated with 14-year change in diastolic BP while rs1935582 and rs2576178 were associated with mean arterial pressure change over 14 years. In addition, SNPs rs796945, rs1935582 and rs2576178 were significantly associated with hypertension incidence. Gene-based analysis found that renalase gene was significantly associated with hypertension incidence over 14-year follow-up after adjustment for multiple measurements.② Hypertensive subjects had higher serum renalase levels than normotensive subjects (27.2±0.4 vs. 25.1±0.2μg/mL). Serum renalase levels and BPs showed a linear correlation. In addition, serum renalase was significantly associated with the risk of hypertension [OR=1.018 (1.006-1.030)]. ③ The expression of renalase in human renal biopsy specimens significantly decreased in hypertensive patients compared to non-hypertensive patients (0.030±0.001 vs. 0.038±0.004). Conclusions: These findings indicate that renalase may play an important role in BP progression and development of hypertension.